MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN KOLASE DENGAN BAHAN BULU AYAM DI TK TUNAS HARAPAN TENGGARONG SEBERANGTAHUN PEMBELAJARAN 2016/2017 - Darwati - Darwati; Hanita - Hanita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
It is important for young learners to develop their sensory motor skill since it influences their skill in daily activities. However, in Tunas Harapan Kindergarten Tenggarong Seberang, the researcher observed that students aged 5-6 years old have low sensory motor skill such as in activities of writing, drawing, and coloring. Therefore, the researcher conducted a classroom action research in Tunas Harapan Kindergarten to find out the effectiveness of collage activity with bird’s feather as the learning median to improve the students’ sensory motor skills. In this study, as the learning media, the researcher did not only use bird’s feather, but also some materials which easily found around the countryside. As the research subjects, the researcher involved twenty students of group B, consisting of twelve males and eight females. Moreover, the data was collected during January to February 2017 by employing observation guide and documentation. Based on the result of research, it is found significant difference on average scores between cycles, before and after the treatment. At cycle I, the students’ sensory motor skill increased at 62.5% which classified in fair category. In addition, at the second cycle, the percentage went up into 75% which classified in good category. In conclusion, collage activity influenced students’ sensory motor skill. Therefore, it is suggested for teachers to provide stimulation and practices to increase students’ sensory motor skill by using various materials.